New Frontiers in Offender Treatment The Translation of Evidence-Based Practices to Correctional Settings (Springer International Publishing, 2018)
This book reviews how new and promising evidence-based interventions are being used with those involved in the criminal justice system. While there has been an increased emphasis on evidence-based practice within forensic treatment, there remains a disjoint between what we know works and adapting these interventions to those involved in the criminal justice system. This book seeks to bridge that gap by providing an overview of what we know works and how that information has been translated into offender treatment. In addition, it highlights avenues where additional research is needed. This book is comprised of three parts: In the first part, current models of correctional treatment including the Risk, Needs, Responsivity Model, The Good Lives Model and Cognitive Behavioral Models are presented. In the second part, the chapters address clinical issues such as the therapeutic alliance, clinician factors, and diversity related issues that impact treatment outcome. In the third and final part of the book, adaptions of innovative and cutting-edge evidence-based treatments such as Dialectical Behavior Therapy, Trauma Informed Care, Mindfulness, Motivational Interviewing, Assertive Community Treatment, Multisystemic Treatment, New frontiers in Intimate Partner Violence treatment, and the current research on the treatment of those with psychopathy are presented. Research supporting these treatment approaches targeting areas such as self-management, psychological well-being, treatment engagement and retention and their relationship to recidivism will be reviewed, while their adaptation for use with forensic populations is discussed. The book concludes with the editors' summary of the findings and a discussion of the future of evidence-based interventions within the field of forensic psychology.